The birth and formation of the concept of personality in psychology - Dosjonova Nilufar Rustam qizi; Bakhtiyorova Munira Mansur qizi (Genius Journals, 2022)
The article tells about the concept of a person and the history of his development. The article cites a variety of scholars, their different perspectives on the individual, and the debates, as well as extensive information about the type of individual. In the summary you can learn about how to develop an individual.
Keywords: Person; individual; philosophical-literary; clinical